151k views
5 votes
Evaluate h(8q2 - 2g) for h(x) = 7x+ 4q

Evaluate h(8q2 - 2g) for h(x) = 7x+ 4q-example-1
User OldPadawan
by
5.7k points

1 Answer

4 votes

Answer:

56q2 - 10q

Explanation:

1. the function is given h(x) = 7x + 4q

2. we should put (8q2 - 2q) instead of x

3. we should write when x = 8q2 - 2q

then it will be h(8q2 - 2q)= 7(8q2 - 2q) + 4q

4. then we should multiply the elements in the bracket with 7 then it will be 56q2 - 14q + 4q

5. then we should substract -14q + 4q then it will be -10

6. and answer comes 56q2 - 10q

User Savepopulation
by
6.1k points